Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s00066-007-1774-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased Radiosensitivity as an Indicator of Genes Conferring Breast Cancer Susceptibility

Abstract: The MNT detects a cellular phenotype common to a portion of sporadic breast cancer patients. This phenotype is very likely to be genetically determined. For the genetic dissection of breast cancer susceptibility this phenotype may turn out to be more efficient than breast cancer itself. Additional parameters which can be measured simultaneously with the MN frequency may be able to further enhance its usefulness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Several other groups have also reported the detection of cell-free EBV-DNA in the serum or plasma of NPC patients and healthy controls, with highly variable detection rates from 31% to 96% for NPC patients and from 0% to 14% for healthy controls [30,35,43]. There are several possibilities to account for these discrepancies, such as the number of PCR amplification cycles, the sensitivity of each PCR technique, the speci- [46] and EBV-DNA detection in peripheral whole blood using PCR with specific primers to amplify the targeted region of the EBNA-1 gene, suggesting the reported association between EBV and NPC could be higher, if different methods of EBV detection were used [12].…”
Section: Discussionmentioning
confidence: 99%
“…Several other groups have also reported the detection of cell-free EBV-DNA in the serum or plasma of NPC patients and healthy controls, with highly variable detection rates from 31% to 96% for NPC patients and from 0% to 14% for healthy controls [30,35,43]. There are several possibilities to account for these discrepancies, such as the number of PCR amplification cycles, the sensitivity of each PCR technique, the speci- [46] and EBV-DNA detection in peripheral whole blood using PCR with specific primers to amplify the targeted region of the EBNA-1 gene, suggesting the reported association between EBV and NPC could be higher, if different methods of EBV detection were used [12].…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies compared the RS of breast cancer patients with control individuals ( Table 1). The majority of studies (77.8%) reported that radiation-induced frequency of micronucleus was significantly higher in breast cancer group in comparison to control [5,10,11,133,135,136,145]. In contrast, Djuzenova et al determined no significant difference between the level of MNi in breast cancer patients and healthy participants using G2 micronucleus test [12] and Francies et al reported breast cancer patients with luminal are more radiosensitive compared to healthy control, while no difference between those with triple-negative breast cancer and healthy control has been detected [132].…”
Section: Radiosensitivity Assays In Breast Cancermentioning
confidence: 99%
“…Studies have reported that BRCA1 −/− mouse embryonic fibroblasts (MEFs) and human breast cancer line, HCC1937 [7,8], are highly sensitive to ionizing radiation and retrovirally transfecting these cells with wild-type BRCA1 diminished the ionizing radiation sensitivity and improved the efficiency of DSBs repair [9]. Likewise, the clinical studies stated BRCA1/2 mutation carriers are more radiosensitive than healthy control [5,10,11] and manifest more severe radiotherapy complications [12,13] due to having defective DNA damage repair system.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro CRS is therefore considered to be a hallmark for BC and a marker for low-penetrant gene mutations predisposing to BC (3,4,6,7,9). The most detrimental form of ionizing radiationinduced DNA damage is the double strand break (DSB) due to its ability to generate chromosomal aberrations when misrepaired or left unrepaired.…”
Section: Introductionmentioning
confidence: 99%